Wat i doświadczenie historyczne - Czajkowska, Agnieszka (Colloquia Litteraria, 2012)
Aleksander Wat and historical experience An exceptionally complex biography of Aleksander Wat, apparently present in his literary output, makes him a person especially privileged that betoken the history of the 20th century. A historical experience constitutes for Wat an artistic problem, literature becomes a record of his experience – a direct and authentic record. However, since writing is not only an ethnic obligation but also the inclusion into a widely understood cultural context, Wat undertakes the attempts of communicating with the world, it becomes though more and more difficult for the poet due to the lack – in his opinion – of a suitable poetic language for the description of the world. The outcome of it is Wat’s reaching the borders of the speech – to silence ([Zakułem się w pancerz myślenia...]). What Wat considered in his experience as the most important, it becomes therefore strengthened not only in his poetry but, above all, in Mój wiek [My Century] – a text not written but spoken, tape recorded; richness (“the excess of information”), digressiveness but also some breaking up, some formal “splitting up” of this text, reflects most fully heterogenous, complicated, full of suffering Wat’s experience. A vitally important in this situation is Czesław Miłosz, Wat’s interlocutor whose discreet presence, wise posing of questions orders the picture drawn chaotically by Wat.